1990
DOI: 10.1029/jc095ic07p11425
|View full text |Cite
|
Sign up to set email alerts
|

A poleward flow along the Atlantic coast of the Iberian peninsula

Abstract: Satellite Advanced Very High Resolution Radiometer (AVHRR) imagery and Argos tracked drifters have revealed the existence of a narrow, warm surface poleward current along the Iberian coast during autumn and winter. Six near‐surface drifter tracks indicated a net northward flow between September 1986 and March 1987, although individual drifter trajectories also provided evidence of eddy activity and episodes of equatorward flow. A SeaSoar survey during September 1986 in the region 37°–43°N, 9°–11°W showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
193
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(205 citation statements)
references
References 15 publications
11
193
0
Order By: Relevance
“…1a). The IPC, extending down to 400 m, transports warm and salt-rich waters of 154 subtropical origin [Frouin et al, 1990;Haynes and Barton, 1990] and can be traced into the Bay 155 of Biscay. The IPC's subsurface or undercurrent part conveys ENACW of subtropical (st) origin 156 poleward year-round.…”
mentioning
confidence: 99%
“…1a). The IPC, extending down to 400 m, transports warm and salt-rich waters of 154 subtropical origin [Frouin et al, 1990;Haynes and Barton, 1990] and can be traced into the Bay 155 of Biscay. The IPC's subsurface or undercurrent part conveys ENACW of subtropical (st) origin 156 poleward year-round.…”
mentioning
confidence: 99%
“…This current, (which is referred to later as the poleward current) has a width of O(25 km) and extends from the surface down to O(200 m). The existence of this feature has been confirmed by satellite imagery, in situ hydrographic measurements and Lagrangian drifters, (Frouin et al, 1990;Haynes and Barton, 1990). According to Frouin et al (1990) only about one fifth of the observed transport of this current can be accounted for by onshore Ekman convergence induced by southerly winds.…”
Section: Oceanography Of the Regionmentioning
confidence: 63%
“…October--November represent a transition in the ecosystem from the summer dominant upwelling situation to the autumn dominant downwelling situation (Álvarez-Salgado et al, 2003;Castro et al, 1997), driven by a shift in the wind regime from northerlies to southerlies. It also coincides with the onset of the relatively warm and saline IPC over the slope (Haynes and Barton, 1990). This shift is usually coincident with a phytoplankton autumn bloom in the coast (Álvarez-Salgado et al, 2003;Bode et al, 1996;Casas et al, 1997;Castro et al, 1997).…”
Section: Elsevier_marsys_2604mentioning
confidence: 99%
“…This fact is usually attributed to an efficient recycling (mineralization) of organic matter under periodic (1--3 weeks) wind stress--relaxation cycles (Álvarez-Salgado et al, 1993;Arístegui et al, 2009). The autumn (October--November) brings a shift to southerly winds, which favors downwelling conditions over the shelf (Álvarez-Salgado et al, 2003), coinciding with the onset of a warm and saline poleward current over the slope, the Iberian Poleward Current (IPC) (Haynes and Barton, 1990). This shift is usually coincident with a phytoplankton autumn bloom in the coast (Álvarez-Salgado et al, 2003;Bode et al, 1996;Casas et al, 1997;Castro et al, 1997).…”
mentioning
confidence: 99%